Development and psychometric properties of health care workers’ concerns in infectious outbreaks scale - Yarahmadi, Sajad; Khademi, Mojgan; Ebrahimzadeh, Farzad; Cheraghian, Tayebeh; Shahidi Delshad, Elham (Frontiers in Psychology, 2023)
Introduction Healthcare workers are a crucial workforce; from a moral perspective, understanding their concerns and how to support them is crucial and makes it possible for health services to keep functioning. This study aimed to develop and validate Health Care Workers’ Concerns in Infectious Outbreaks Scale (HCWCIOS). Methods This exploratory sequential mix-method study was employed to design and validate the HCWCIOS. The initial tool was designed after searching similar studies and performing a qualitative phase under the semi-structured approach. Both qualitative and quantitative methods were used to evaluate the face and content validity. The content validity ratio, content validity index, and item-level content validity index were also calculated. Exploratory factor analysis was employed to evaluate the construct validity. Using a convenient sampling method, 354 Iranian healthcare workers participated in the study. Computing Cronbach’s alpha coefficient estimated the internal consistency for HCWCIOS and its subscales. Furthermore assessed was test–retest reliability. Results The preliminary scale was designed with 57 items. By eliminating nine items in the content validity phase and 12 items during factor analysis, the final 36-item scale was developed on six factors: inadequate preparedness, lack of knowledge, risk perception, affected social relations, work pressure, and absenteeism. These six factors accounted for 46.507% of the total variance. The whole scale’s Cronbach’s alpha coefficient was 0.912, and the intra-class correlation coefficient was 0.88. Conclusion A 36-item HCWCIOS has good psychometric properties and is suitable for measuring healthcare workers’ concerns during a pandemic.